Acetylene-bridged triazine π-conjugated structures: synthesis and liquid crystalline properties - Akkurt, Nihat; Al-Jumaili, Mohammed Hadi Ali; Bilgin Eran, Belkiz; Ocak, Hale; Torun, Lokman (Tubitak Scientific & Technological Research Council Turkey, 2019)
We report the synthesis and liquid crystalline properties of a new type of tribranched compound built up from triazine as the central core and electron-rich triazine rings as peripheral groups. An equimolar mixture of the star-shaped compound based on the 1,3,5-triazine core with 4-dodecyloxybenzoic acid produced an organic salt exhibiting a columnar mesophase with a dendritic growing texture at low temperatures. The liquid crystalline properties of the triazine-based compound and organic salt were investigated by differential scanning calorimetry and polarizing optical microscopy.
Keywords: Triazine; liquid crystals; star-shaped materials; hydrogen bonding; G PHASE; BEHAVIOR; SERIES; Chemistry; Engineering